The Prossesing Transformation of Sago (Sumaku) in Tolaki Communityat Anggolomoare village in Konawe Regency - Bobiy, Bobiy; Suardika, I Ketut; Alim, Abdul (Jurnal Penelitian Budaya, 2020)
This study aimed to describe the form of transformation of processing of sago (sumaku) from the Traditional to Semi-Modern Processing, and analyzing the factors that caused it to transform processing of food for Tolaki community at Anggalomoare village of Konawe Regency. The method used in this study is qualitative methods, from which the data is obtained through participatory observation, and interviews, as well as observations on research objects, then analyzed by qualitative descriptive. The results of this research showed that the transformation of sago processing (sumaku) consist of technological changes used from traditional tools to semi-modern tools, while the factors that influence transformation of processing sago (sumaku) in Tolaki community are caused by Economic, Educational and Technological factors. Modern processing has advantages including more production results, time utilization is more effective and efficient when compared to traditional methods.Keywords: Transformation, Processing of Sago (Sumaku), Tolaki community